Sistem Informasi Manajemen Pelatihan dengan Pendekatan Research and Development di Balai PPM Pekanbaru - Reny Fitri Yani; Rahmat Hidayat; Mirdatul Husnah; Yanti Andriyani; Ayu Andria (Universitas Methodist Indonesia, 2025)
Adaptation to the rapid development of information technology today is something that cannot be avoided by government agencies. The Pekanbaru Community Empowerment and Training Center (Balai PPM Pekanbaru) is one of the agencies that can easily adapt to these developments. The problem faced by Balai PPM Pekanbaru is the large number of training participants in five provinces in Sumatra, making it difficult to manage training participants. This study aims to create an information system for managing training participants at Balai PPM Pekanbaru. The method used in this study is the Research and Development method. The results of the research that has been carried out are to help the Balai PPM Pekanbaru admin in managing training participants easily so that all data is centralized in a system that can work more easily and efficiently.